2020
DOI: 10.2147/ott.s249853
|View full text |Cite|
|
Sign up to set email alerts
|

<p>circPDSS1 Stimulates the Development of Colorectal Cancer via Activating the Wnt/β-Catenin Signaling</p>

Abstract: This study aims to illustrate the role of circPDSS1 and the Wnt/β-catenin signaling in the development of colorectal cancer (CRC). Patients and Methods: Cancerous mucosa and normal paracancerous mucosa tissues more than 5 cm away from the tumor were surgically collected from 56 CRC patients. circPDSS1 levels in collected tissues and CRC cell lines were detected by quantitative real-time polymerase chain reaction (qRT-PCR). The influence of circPDSS1 on clinical features of CRC patients was analyzed. After knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Fang et al pointed out that circPDSS1 was upregulated in colorectal cancer tissues and circPDSS1 promoted migratory ability and angiogenesis in colorectal cancer cells via activating Wnt/β-catenin signaling. 32 In addition, Yu et al declared that circPDSS1 promoted the development of bladder cancer via downregulation of miR-16. 33 More importantly, Ouyang et al revealed that circPDSS1 was upregulated in GC tissue samples and cell lines, and knockdown of circPDSS1 repressed GC cell proliferation and accelerated apoptosis via sponging miR-186-5p and regulating NEK2.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al pointed out that circPDSS1 was upregulated in colorectal cancer tissues and circPDSS1 promoted migratory ability and angiogenesis in colorectal cancer cells via activating Wnt/β-catenin signaling. 32 In addition, Yu et al declared that circPDSS1 promoted the development of bladder cancer via downregulation of miR-16. 33 More importantly, Ouyang et al revealed that circPDSS1 was upregulated in GC tissue samples and cell lines, and knockdown of circPDSS1 repressed GC cell proliferation and accelerated apoptosis via sponging miR-186-5p and regulating NEK2.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrantly expressed ncRNAs have been demonstrated to be associated with cRc tumorigenesis (25,(62)(63)(64)(65)(66)(67). Additionally, the aberrant expression of ncRNAs is correlated to the clinicopathological characteristics of cRc, such as prognosis (68), survival (69,70) and metastasis (1,7,8,62,(71)(72)(73)(74)(75). In the present review, the aberrant expression of ncRNAs and their effects on cRc in the Wnt/β-catenin signaling pathway are presented in Table I (5,7,8,25,36,(62)(63)(64)(65)(66)(67)(68)(69)(70).…”
Section: Abnormality Of Non-coding Rnas (Ncrnas)mentioning
confidence: 99%
“…The exact mechanisms of the functional roles of circRNA in CRC remain elusive. Additionally, the upregulation of circRNA-PDSS1 promotes migratory ability and angiogenesis in CRC cells via the upregulation of β-catenin, c-Myc, cyclin D1 and MMP-9, leading to lymphatic metastasis and distant metastasis ( 75 ).…”
Section: Role Of Wnt/β-catenin Signaling In Colorectal Cancer (Crc)mentioning
confidence: 99%
“…Up to date, it has been reported that multiple molecules and mechanisms (eg VEGF/ VEGFR2 signalling, 47 MAPK, 48 Notch signalling 49 and Wnt/β‐catenin signalling 50 ) are involved in tumour angiogenesis. Also, accumulating studies find that tumour‐derived EVs contain proteins related to the signalling pathways mentioned above, thus making the EVs a vital role in tumour angiogenesis.…”
Section: Tumour‐derived Evs Regulating Angiogenesis Via Non‐coding Rnmentioning
confidence: 99%
“…Up to date, it has been reported that multiple molecules and mechanisms (eg VEGF/ VEGFR2 signalling, 47 MAPK, 48 Notch signalling 49 and Wnt/β-catenin signalling 50 ) are involved in tumour angiogenesis.…”
Section: The Angiogenic-related Proteins In Tumourderived Evsmentioning
confidence: 99%